2021
DOI: 10.3390/nu13093003
|View full text |Cite
|
Sign up to set email alerts
|

Association between Food Preferences and Food Habits in a Polish Adolescents’ COVID-19 Experience (PLACE-19) Study

Abstract: Food preferences are among the most influential factors of food habits in the vulnerable period of adolescence; in addition, gender-dependent differences in food preferences are also observed. The aim of the present study was to analyze differences in food habits between individuals stratified based on their food preferences in a population-based sample of adolescents aged 15–20. The study was conducted within the Polish Adolescents’ COVID-19 Experience (PLACE-19) Study population in a group of 2419 secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The PLACE-19 Study, which analyzed the various aspects of the life of Polish adolescents (aged 15-20, a typical age for education in the secondary school) in the period of the COVID-19 pandemic, was divided into three phases. During the first phase of the study, the hygienic and personal protective behaviors of adolescents were investigated [22][23][24], while in the second and third phase their eating habits [25][26][27][28][29][30] and psychological aspects of eating behaviors were analyzed, respectively.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PLACE-19 Study, which analyzed the various aspects of the life of Polish adolescents (aged 15-20, a typical age for education in the secondary school) in the period of the COVID-19 pandemic, was divided into three phases. During the first phase of the study, the hygienic and personal protective behaviors of adolescents were investigated [22][23][24], while in the second and third phase their eating habits [25][26][27][28][29][30] and psychological aspects of eating behaviors were analyzed, respectively.…”
Section: Study Populationmentioning
confidence: 99%
“…The mean age in the studied group was 16.7 ± 1.13 years (median of 17.0, differing from 15.0 to 20.0; nonparametric distribution), and it did not differ between female (16.7 ± 1.14 years, median of 17.0, differing from 15.0 to 20.0; nonparametric distribution) and male individuals (16.7 ± 1.10 years, median of 16.5, differing from 15.0 to 20.0; nonparametric distribution) (Mann-Whitney U test, p = 0.4110). while in the second and third phase their eating habits [25][26][27][28][29][30] and psychological aspects of eating behaviors were analyzed, respectively. The study of psychological aspects of eating behaviors was carried out from 21 January 2021 to 17 February 2021.…”
Section: Study Populationmentioning
confidence: 99%
“…The AFHC [37] is based on 23 questions about various food habits, which are associated with food purchase, preparation, and consumption. The Polish version of AFHC was applied as it is commonly used [41,42], and was developed based on the forward and backward translation and transcultural adaptation [41].…”
Section: Applied Questionnairementioning
confidence: 99%
“…Among various tools used to assess food habits, one of the commonly used questionnaires is the Adolescent Food Habits Checklist (AFHC) by Johnson et al [37], which is used not only for adolescents [38,39] but also for adults [40]. This questionnaire was already used to assess the changes of food habits during the COVID-19 pandemic in the population of older adolescents [41,42], and studies revealed that while some food habits were improved, the other ones were worsened, which enabled defining essential areas for public health education [41]. In populations of younger adolescents [37,38], or even children [39], this tool was also used in multiple studies, but it has not been used so far in this population during the COVID-19 pandemic to assess their food habits changes.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that consuming calcium‐fortified foods can help the elderly to improve their nutritional status and quality of life and prevent deficiencies. Consumption of fortified food products by adolescents as an alternative to popular snacks may also affect the individuals' health, such as weight and nutritional status, and in the future affect eating behavior and food preferences 8‐10 . The arguments in favor of the use of eggshells in the design of calcium‐fortified products are: high calcium content in the eggshell (about 38 g kg −1 ); almost three times greater bioavailability of calcium compared to synthetic CaCO 3 in animal models; 11 and statistically significantly higher calcium absorption, as shown in studies among postmenopausal women 12 .…”
Section: Introductionmentioning
confidence: 99%